Leakage of Public Resources in the Health Sector : An Empirical Investigation of Chad - Gauthier, Bernard; Wane, Waly (2012)
In the public sector in developing countries, leakage of public resources could prove detrimental to users and affect the well-being of the population. This paper empirically examines the importance of leakage of government resources in the health sector in Chad, and its effects on the prices of drugs. The analysis uses data collected in Chad as part of a Health Facilities Survey organized by the World Bank in 2004. The survey covered 281 primary health care centers and contained information on the provision of medical material, financial resources, and medicines allocated by the Ministry of Health to the regional administration and primary health centers. Although the regional administration is officially allocated 60 percent of the ministry's non-wage recurrent expenditures, the share of the resources that actually reach the regions is estimated to be only 18 percent. The health centers, which are the frontline providers and the entry point for the population, receive less than 1 percent of the ministry's non-wage recurrent expenditures. Accounting for the endogeneity of the level of competition among health centers, the leakage of government resources has a significant and negative impact on the price mark-up that health centers charge patients for drugs.